2012
DOI: 10.1213/ane.0b013e31824f92c2
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Ketorolac After Single Postoperative Intranasal Administration in Adolescent Patients

Abstract: Administration of ketorolac by the intranasal route resulted in a rapid increase in plasma concentration and may be a useful therapeutic alternative to IV injection in adolescents because plasma concentrations attained with the device are likely to be analgesic (investigational new drug no. 62,829).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…h −1 ) revealed that clearance decreases from infancy to adolescence. This change with age for ketorolac has been described by others …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…h −1 ) revealed that clearance decreases from infancy to adolescence. This change with age for ketorolac has been described by others …”
Section: Discussionsupporting
confidence: 77%
“…The pharmacokinetics (PK) of ketorolac changes with age in children . The main contributors to reported pharmacokinetic variability in children are maturation of organ systems (reflected by age) and size effects .…”
Section: Introductionmentioning
confidence: 99%
“…The mean time to peak concentration using the intranasal route was 52 minutes, with a standard deviation of six minutes. A target concentration of 0.37 mg/L in the effect compartment was achieved within 30 minutes and remained above that target for 10 hours . An analysis of the postoperative analgesia provided by ketorolac in adults showed an estimated effect compartment with 50% effective concentration of 0.37 mg/L.…”
Section: Introductionmentioning
confidence: 93%
“…Animal studies have shown that the antiinflammatory activity of Ketorolac resides in the (−) S entantiomer and that the (+) R entantiomer is pharmacologically inactive [7]. The pharmacokinetics of Ketorolac has been documented in humans [8][9][10][11][12][13][14][15] and animals including dogs [16], rats [17], calves [18], rabbits [19], goats [20], and sheep [21]. Objectives of this study was to determine the difference of tissue distribution of Ketorolac and its enantiomers in rats following a single oral dose of 3.2 mg/kg racemic mixture.…”
Section: Introduction ▼mentioning
confidence: 99%